A new energy catalyst, preparation method and application thereof

By introducing cyano and phenyladehyde groups into carbon nitride materials, the ABTA-DC3N4-ACN photocatalyst is solved, and the carbon nitride materials are low in efficiency in the photocatalytic hydrogen peroxide production process is achieved, and more efficient photocatalytic production efficiency is achieved.

CN118751282BActive Publication Date: 2025-03-28HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410739374.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-03-28
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

In the process of photocatalyzing hydrogen peroxide production, carbon nitride materials have problems such as high recombination rate of photogenerated electron-hole pairs and low quantum efficiency, which leads to low production efficiency, which limits its further application in the field of photocatalysis.

Method used

By introducing cyano (-CN) and phenyladetrialdehyde groups, donor-acceptor type carbon nitride photocatalytic material ABTA-DC3N4-ACN is formed, improving its light absorption and carrier separation efficiency.

Benefits of technology

The absorption of carbon nitride materials to light at wavelengths below 450 nm is improved, the recombination of photogenerated electrons and holes is suppressed, the photocurrent response is enhanced, and the efficiency of hydrogen peroxide production is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118751282B_ABST
    Figure CN118751282B_ABST
Patent Text Reader

Abstract

The present invention provides a new energy catalyst, a preparation method and an application thereof. 3 N 4 and sodium thiocyanate as the starting materials, which are pyrolyzed to generate g‑C 3 N 4 ‑CN; then g‑C 3 N 4 ‑CN is mixed with benzene trimeraldehyde and heat treated to obtain A BTA ‑D C3N4 ‑A CN The A obtained by the above preparation method BTA ‑D C3N4 ‑A CN New energy catalysts, and g‑C 3 N 4 Compared with the catalyst, the introduction of cyano and trimesic acid groups makes the newly formed photocatalyst significantly enhance the light absorption of wavelengths below 450nm; at the same time, the electron-hole pair recombination process is ‑ ) are transferred to the cyano group and the trimesic group respectively. The capture of electrons by the two makes it difficult for the photogenerated electrons and holes to recombine. The introduction of the cyano group (-CN) and the trimesic group promotes the generation of photogenerated carriers and inhibits the recombination of photogenerated carriers, making A BTA ‑D C3N4 ‑A CN It has better carrier separation efficiency and shows stronger photocurrent response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy catalytic materials and the technical field of solar energy conversion, and in particular to a new energy catalyst, a preparation method and application thereof. Background Art

[0002] Hydrogen peroxide is one of the 100 most important chemicals in the world. The global production of hydrogen peroxide in 2020 was about 4 million tons, and it is expected to reach 5.7 million tons by 2027. As a clean oxidant, hydrogen peroxide is widely used in various fields such as chemical synthesis, pulp bleaching, disinfection and environmental remediation. In addition to being used as an oxidant, hydrogen peroxide can also be used as a chemical fuel to drive hydrogen peroxide fuel cells. Hydrogen peroxide has broad application prospects in the fields of energy and environment. The clean production of hydrogen peroxide has also attracted widespread attention from researchers. Currently, more than 95% of hydrogen peroxide is produced by the anthraquinone method. However, the traditional anthraquinone method for producing hydrogen peroxide has problems such as high energy consumption, environmental pollution, safety risks, low efficiency, and high transportation costs.

[0003] Photocatalysis is a promising renewable energy conversion technology that can convert the abundant solar energy (1.3×105TW) reaching the earth's surface into storable chemical energy. This technology has been used for water decomposition to produce hydrogen, CO2 reduction to produce carbon-based fuels or chemicals, and pollutant degradation. Recently, it has been found that the use of suitable semiconductors can reduce dissolved oxygen in water to hydrogen peroxide through photocatalysis. Compared with traditional methods, photocatalytic production of hydrogen peroxide can directly utilize solar energy, which has the advantages of being green and efficient.

[0004] Among many semiconductor catalysts, people have found that unlike traditional semiconductor materials such as titanium dioxide and zinc oxide that can only absorb ultraviolet light, the band gap width of graphite phase carbon nitride is 2.7eV, which makes it also have a photocatalytic effect in the visible light range. The conduction band potential of carbon nitride is -1.3V, which is more negative than the potential of O2 reduction to H2O2 (0.695V). Therefore, the photogenerated electrons on the conduction band of carbon nitride can reduce oxygen to hydrogen peroxide. Graphite phase carbon nitride has a layered structure similar to graphite, and there are strong van der Waals forces between layers, which makes carbon nitride have stable chemical properties. In addition, carbon nitride can be prepared by thermal reaction using low-cost nitrogen-rich substances such as dicyandiamide, melamine and urea, and the preparation cost is low. It is an ideal catalyst for photocatalytic production of hydrogen peroxide.

[0005] However, carbon nitride still has the defects of high recombination rate of photogenerated electron-hole pairs and low quantum efficiency. Therefore, its efficiency in producing hydrogen peroxide is not high. This problem restricts the further application and development of carbon nitride in the field of photocatalytic hydrogen peroxide production. Summary of the invention

[0006] In order to improve the efficiency of photocatalytic production of hydrogen peroxide by existing carbon nitride materials, the present invention provides a donor-acceptor type carbon nitride photocatalytic material with visible light response, a preparation method and application thereof, which has the ability to efficiently catalyze water molecules to produce hydrogen peroxide and can be used to construct an energy-saving photocatalytic system.

[0007] The specific content of the invention is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a new energy catalyst, the preparation method comprising the following steps:

[0009] S1: After g-C3N4 and sodium thiocyanate are uniformly mixed, they are placed in a nitrogen atmosphere and pyrolyzed at 400-600°C for 3-5h. The reaction product is cooled, washed and dried to obtain the precursor material g-C3N4-CN;

[0010] S2: The ground precursor g-C3N4-CN and trimesic acid aldehyde are added to an acetonitrile solution for ultrasonic dispersion, and heated in an oil bath at 80-120°C for 10-14h under magnetic stirring. The reaction product is cooled, washed and dried to obtain the new energy catalyst A. BTA -D C3N4 -A CN .

[0011] Optionally, in step 1, the uniformly mixing of g-C3N4 and sodium thiocyanate comprises: after mixing g-C3N4 and sodium thiocyanate, adding a small amount of water and stirring to allow sodium thiocyanate to fully contact g-C3N4, and then placing the mixture in an oven for drying.

[0012] Optionally, in step 1, the mass ratio of g-C3N4 to sodium thiocyanate is between 1:0.5-1.5.

[0013] Optionally, in step 1, the washing and drying treatment comprises: washing the reaction product 3-5 times with anhydrous ethanol and deionized water alternately, and then placing the product in an oven and drying it at 50-70°C.

[0014] Optionally, in step 2, the particle size of the precursor material g-C3N4-CN after grinding is between 200-400 mesh.

[0015] Optionally, in step 2, the mass ratio of the precursor material g-C3N4-CN to the trimesaldehyde is between 1:1-2.

[0016] Optionally, in step 2, the ultrasonic dispersion time is between 0.5-1h;

[0017] The washing and drying treatment comprises: washing the reaction product with acetonitrile for 3-5 times, and then placing the product in an oven and drying it at 50-70°C.

[0018] Optionally, the g-C3N4 is obtained by calcining melamine as a raw material in an air atmosphere;

[0019] The calcination temperature is between 500-600° C. and the calcination time is between 3-6 hours.

[0020] In a second aspect, the present invention provides a new energy catalyst obtained by the preparation method described in the first aspect.

[0021] In a third aspect, the present invention provides an application of a new energy catalyst obtained in the first aspect, wherein the new energy catalyst is used to catalyze air / oxygen to produce hydrogen peroxide; in the process of catalyzing air / oxygen to produce hydrogen peroxide, p-methoxybenzyl alcohol is used as an electron donor.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] The present invention provides a method for preparing a new energy catalyst, comprising: mixing g-C3N4 and sodium thiocyanate uniformly, placing in a nitrogen atmosphere, pyrolyzing for 3-5 hours, cooling, washing and drying the reaction product to obtain a precursor material g-C3N4-CN; adding the ground precursor material g-C3N4-CN and trimesic acid to an acetonitrile solution for ultrasonic dispersion, and placing in an oil bath pot at 80-120°C for heating for 10-14 hours under magnetic stirring, cooling, washing and drying the reaction product to obtain the new energy catalyst-A BTA -D C3N4 -A CN Compared with the original g-C3N4 catalyst, the new energy catalyst obtained by the above preparation method has a significantly enhanced light absorption of wavelengths below 450nm due to the introduction of cyano (-CN) and trimesic acid groups. At the same time, the introduction of -CN and trimesic acid groups makes the electron-hole pair recombination process more electrons (e - ) are transferred to the cyano group and the trimesic group, respectively. The capture of electrons by the two groups makes it difficult for the photogenerated electrons and holes to recombine. Furthermore, compared with the original g-C3N4 photocatalyst, A BTA -D C3N4 -A CN It shows a stronger photocurrent response, which indicates that the introduction of cyano (-CN) and trimesic acid groups promotes the generation of photogenerated carriers and inhibits the recombination of photogenerated carriers, thus having a better carrier separation efficiency.

[0024] When the new energy catalyst provided by the present invention is used to catalyze the production of hydrogen peroxide from air / oxygen, p-methoxybenzyl alcohol is used as an electron donor to catalyze the conversion of oxygen / air into hydrogen peroxide under natural light conditions; during the reaction, p-methoxybenzyl alcohol is first adsorbed on the surface of the new energy catalyst, and then reacts with the photogenerated holes and free radicals on the active sites of the catalyst to be converted, and at the same time, the photogenerated electrons exposed on the active sites of the catalyst combine with oxygen molecules to produce various free radicals to complete the generation of hydrogen peroxide. Finally, oxygen and water generate hydrogen peroxide under the action of the catalyst. Experimental conditions have shown that when a xenon lamp is used as the light source and the light intensity is 100mW / cm 2 Under the irradiation of visible light (λ>400nm), the dosage of the donor-acceptor carbon nitride photocatalyst provided by the present invention is 10mg, the concentration of p-methoxybenzyl alcohol is 10mM, the initial temperature is room temperature, and the pH is 9, A BTA -D C3N4 -A CN The photocatalytic material produced a hydrogen peroxide concentration of 3.782mmol / L after 60 minutes, which is much higher than that of similar photocatalysts. After repeated use, the photocatalytic performance of the material is stable, and a large amount of hydrogen peroxide can be produced under long-term illumination, which has practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The flowchart of the method for preparing a new energy catalyst provided by an embodiment of the present invention is shown;

[0027] Figure 2 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN SEM images of new energy catalytic materials;

[0028] Figure 3 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN TEM images of new energy catalytic materials;

[0029] Figure 4 The g-C3N4, g-C3N4-CN and A prepared in Example 1 of the present invention are shown. BTA -DC3N4 -A CN XRD result diagram of

[0030] Figure 5 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN XPS spectrum of

[0031] Figure 6 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN N2 adsorption-desorption isotherm diagram;

[0032] Figure 7 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN Ultraviolet diffuse reflectance spectrum of

[0033] Figure 8 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN PL spectrum of

[0034] Fig. 9 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN Transient photocurrent response diagram;

[0035] Fig.10 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN In-situ Fourier transform infrared images;

[0036] Fig.11 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN Fourier transform infrared spectrum of

[0037] Fig.12 A prepared in the embodiment of the present invention is shown BTA -D C3N4 -A CNPhotocatalytic hydrogen peroxide production performance;

[0038] Fig.13 A prepared in Examples 1-5 of the present invention is shown BTA -D C3N4 -A CN Photocatalytic hydrogen peroxide production performance;

[0039] Fig.14 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The production of hydrogen peroxide by new energy catalytic materials under different gas atmospheres;

[0040] Fig.15 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The effect of the amount of new energy catalytic materials on hydrogen peroxide production;

[0041] Fig.16 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The production of hydrogen peroxide by new energy catalytic materials at different pH values;

[0042] Fig.17 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN Results of recycling experiments on new energy catalytic materials. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.

[0044] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0045] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.

[0046] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0047] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0048] The present invention improves the defects of g-C3N4 catalytic material, such as high recombination rate of photogenerated electron-hole pairs and low quantum efficiency, and improves its efficiency in catalytic production of hydrogen peroxide. The invention uses a distributed introduction method to sequentially introduce cyano (-CN) and trimesic acid groups into the interlayer structure of g-C3N4 to form a layered stacked new energy catalytic material. The obtained carbon nitride-based new energy catalyst—A BTA -D C3N4 -A CN Compared with the original g-C3N4 catalyst, the introduction of cyano (-CN) and trimesic acid groups makes A BTA -D C3N4 -A CN The light absorption of wavelengths below 450nm is significantly enhanced; at the same time, the introduction of -CN and trimesic acid groups makes the electron-hole pair recombination process - ) are transferred to the cyano group and the trimesic group, respectively. The capture of electrons by the two groups makes it difficult for the photogenerated electrons and holes to recombine. Furthermore, compared with the original g-C3N4 catalyst, A BTA -D C3N4 -A CNIt shows a stronger photocurrent response, which indicates that the introduction of cyano (-CN) and trimesic acid groups promotes the generation of photogenerated carriers and inhibits the recombination of photogenerated carriers, and has a better carrier separation efficiency. The specific implementation is as follows:

[0049] In a first aspect, the present invention provides a method for preparing a donor-acceptor type carbon nitride photocatalyst. Figure 1 The flowchart of the preparation method of the donor-acceptor type carbon nitride photocatalyst provided in the embodiment of the present invention is shown as follows: Figure 1 As shown, the preparation method comprises the following steps:

[0050] S1: After g-C3N4 and sodium thiocyanate are evenly mixed, they are placed in a nitrogen atmosphere and pyrolyzed at 400-600°C for 3-5h. The reaction product is cooled, washed and dried to obtain the precursor material g-C3N4-CN.

[0051] In this step, g-C3N4 can be obtained by calcining melamine as a raw material in an air atmosphere; the calcination temperature is between 500-600°C and the time is between 3-6h; in a specific example, 10g of melamine is ground and pyrolyzed in an air atmosphere at 550°C in a muffle furnace at a heating rate of 5°C / m5n for 4 hours. After cooling, the sample is washed 3 times with deionized water and dried at 60°C to obtain the material g-C3N4.

[0052] The uniform mixing of g-C3N4 and sodium thiocyanate is related to whether the cyano group (-CN) can be uniformly loaded on the g-C3N4 sheet structure during the pyrolysis process. For this reason, in this step, after mixing g-C3N4 and sodium thiocyanate, a small amount of water is added and stirred to make the sodium thiocyanate fully contact the g-C3N4, and then the mixture is placed in an oven for drying to remove moisture so that the g-C3N4 and sodium thiocyanate are uniformly mixed. The mass ratio of g-C3N4 to sodium thiocyanate is between 1:0.5-1.5, and can be specifically selected from any ratio relationship of 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4 and 1:1.5.

[0053] Furthermore, in this step, the pyrolysis temperature can be selected from any one of 400°C, 450°C, 500°C, 550°C and 600°C, and the pyrolysis time can be selected from any one of 3h, 3.5h, 4h, 4.5h and 5h.

[0054] S2: The ground precursor g-C3N4-CN and trimesic acid were added to the acetonitrile solution for ultrasonic dispersion, and heated in an oil bath at 80-120°C for 10-14h under magnetic stirring. The reaction product was cooled, washed and dried to obtain a new energy catalyst - A. BTA -D C3N4 -A CN .

[0055] In this step, the particle size of the ground precursor material g-C3N4-CN is between 200-400 meshes; the ground precursor material g-C3N4-CN and trimesic acid are ultrasonically dispersed in an acetonitrile solution, and the mass ratio of the precursor material g-C3N4-CN to trimesic acid is between 1:1-2. The two are fully mixed by ultrasonic treatment, and then heated in an oil bath at a temperature of 80-120°C for 10-14h to successfully introduce the trimesic acid group into the g-C3N4-CN structure to form A BTA -D C3N4 -A CN New energy catalyst.

[0056] In a second aspect, the present invention provides a new energy catalyst obtained by the preparation method of the first aspect.

[0057] In a third aspect, the present invention provides an application of the new energy catalyst obtained in the first aspect, specifically for catalyzing air / oxygen to produce hydrogen peroxide.

[0058] In the specific implementation, in the process of catalyzing oxygen to produce hydrogen peroxide, p-methoxybenzyl alcohol is used as an electron donor and oxygen is used as a gas atmosphere. A xenon lamp is used as a light source with a light intensity of 100 mW / cm 2 Under the conditions of visible light (λ>400nm), catalyst dosage of 10mg, p-methoxybenzyl alcohol concentration of 10mM, initial temperature of room temperature, and pH of 9, A BTA -D C3N4 -A CN The new energy catalytic material produced hydrogen peroxide at a concentration of 3.782 mmol / L after 60 minutes, which is much higher than that of similar new energy catalysts.

[0059] In order to enable those skilled in the art to more clearly understand the present invention, a new energy catalyst, a preparation method and applications thereof described in the present invention are now described in detail through the following examples.

[0060] Melamine (C3N3(NH2)3), sodium thiocyanate (NaCNS), trimesaldehyde (C9H6O3), and anhydrous ethanol (C2H6O) used in the examples were purchased from Aladdin (Shanghai, China). All reagents were used without further purification. Deionized water was used in all experiments.

[0061] Example 1

[0062] Step 1: After 10 g of melamine was ground, it was pyrolyzed in a muffle furnace at 550 °C in an air atmosphere at a heating rate of 5 °C / m5n for 4 h. After cooling, the sample was washed 3 times with deionized water and dried at 60 °C to obtain the material g-C3N4.

[0063] Step 2: 1g g-C3N4 was ground to 400 mesh, mixed with 1g sodium thiocyanate in the presence of a small amount of water, and then dried in an oven at 600 degrees Celsius, and then pyrolyzed in a nitrogen atmosphere at 400°C in a tube furnace at a heating rate of 5°C / m5n for 3 hours. After cooling, the material was washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C to obtain the precursor material g-C3N4-CN.

[0064] Step 3: 0.1 g of the precursor g-C3N4-CN was ground and mixed with 0.12 g of trimesaldehyde in 100 ml of acetonitrile, and then ultrasonicated for 30 min and magnetically stirred in an oil bath at 80 degrees Celsius for 12 hours. After cooling, the material was washed with acetonitrile 6 times and dried at 60°C to obtain the final material A. BTA -D C3N4 -A CN .

[0065] Figure 2 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN SEM images of new energy catalytic materials, such as Figure 2 As shown, A BTA -D C3N4 -A CN New energy catalytic materials are in block form.

[0066] Figure 3 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN TEM images of new energy catalytic materials, such as Figure 3 As shown, A BTA -D C3N4 -A CN The new energy catalytic materials are stacked in layers with an interlayer spacing of 0.3nm.

[0067] Figure 4 The g-C3N4, g-C3N4-CN and A prepared in Example 1 of the present invention are shown. BTA -D C3N4 -A CNThe XRD results are as follows: Figure 4 As shown, the strong peaks at 27.5° correspond to the (100) and (002) planes, respectively, corresponding to the interlayer stacking of the conjugated aromatic system, A BTA -D C3N4 The peak intensity and peak width of -CAN at 27.5° decreased to a certain extent compared with g-C3N4 and g-C3N4-CN, indicating that the interlayer spacing increased slightly. This may be because different connectors were introduced into the triazine ring unit, resulting in poor planar periodicity. The disordered in-plane structure and interlayer structure are beneficial to the separation of electrons and holes to a certain extent.

[0068] Figure 5 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN The XPS spectrum of Figure 5 As shown in Figure 2, in the g-C3N4-CN sample, the peak at 286 eV gradually increases. This peak is the characteristic peak of cyano, indicating the successful introduction of cyano. BTA -D C3N4 -A CN In the C1s spectrum of the sample, the peak at 286.6eV decreases, indicating a reduction in amino groups, part of which is converted to the characteristic peak of cyano at 286eV. After the introduction of trimesaldehyde, the electron cloud density shifts, and the cyano group is more electron-absorbing than the trimesaldehyde group. At this time, the electron cloud density of the carbon peak at 286.3eV becomes higher, and the excitation binding energy becomes lower, resulting in a decrease in the peak intensity at 286.3eV. In summary, XPS characterization strongly proves the successful introduction of cyano and trimesaldehyde.

[0069] Figure 6 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN The N2 adsorption-desorption isotherm diagram is shown in Figure 6 As shown, in the process from g-C3N4g→C3N4-CN→A BTA -D C3N4 -A CN During the synthesis process, the specific surface area first increases and then decreases. Combined with the XRD pattern, it can be explained that during the synthesis process, the surface of the material tends to be disordered, resulting in an increase in surface energy, and the material is more inclined to curl up to reduce the surface energy.

[0070] Figure 7 The g-C3N prepared in Example 1 of the present invention is shown. 4、g-C3N4-CN and A BTA -D C3N4 -A CN The ultraviolet diffuse reflectance spectrum of Figure 7 As shown, it can be seen that after modification, the light absorption of the material for wavelengths below 450nm is significantly enhanced.

[0071] Figure 8 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN The PL spectrum of Figure 8 As shown in Figure 2, the PL intensity can reflect the charge recombination process of light-induced e- and h+. The higher the PL intensity, the faster the recombination rate of electron-hole pairs. BTA -D C3N4 -A CN The emission peak intensity of is much lower than that of g-C3N4. This may be because after modification, the electrons are transferred to the cyano group and the trimesic group respectively, and the capture of electrons by the two makes it difficult for the photogenerated electrons and holes to recombine.

[0072] Fig. 9 The g-C3N prepared in Example 1 of the present invention is shown. 4、 g-C3N4-CN and A BTA -D C3N4 -A CN The transient photocurrent response diagram is as follows: Fig. 9 As shown, compared with g-C3N4, g-C3N4-CN and A BTA -D C3N4 -A CN It shows a stronger photocurrent response, which indicates that the introduction of cyano (-CN) and trimesic groups can promote the generation of photogenerated carriers and inhibit the recombination of photogenerated carriers. BTA -D C3N4 -A CN It can promote carrier separation and has good carrier separation efficiency, which is consistent with the results of PL spectrum.

[0073] Fig.10 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN In-situ Fourier transform infrared images, such as Fig.10 As shown in Figure 2, without light exposure, the p-methoxybenzyl alcohol in the solution did not bind to the surface of the material (1500 cm -1 ), with the light source turned on and the irradiation time increased, the characteristic peak of the benzene ring (1500cm -1) gradually increases, and more p-methoxybenzyl alcohol is combined with new energy catalytic materials on the surface.

[0074] Fig.11 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The Fourier transform infrared spectrum of Fig.11 As shown, at 1627cm -1 The peaks at 1600, 1311, and 1213 cm -1 The peak at 807cm is derived from the aromatic CN stretching vibration. -1 The peak at corresponds to the breathing mode of the triazine unit.

[0075] Example 2

[0076] The method is the same as in Example 1, except that in step 2, 1 g of g-C3N4 is mixed with 0.8 g of sodium thiocyanate to obtain the precursor g-C3N4-0.8CN, and then step 3 is continued to obtain 1.2A BTA -D C3N4 -0.8A CN .

[0077] The A prepared in this example BTA -D C3N4 -A CN The trends of the SEM images, TEM images, XRD result diagrams, XPS spectra, N2 adsorption-desorption isotherms, UV diffuse reflectance spectra, PL spectra, transient photocurrent response diagrams, in-situ Fourier infrared images and Fourier transform infrared spectra of the donor-acceptor type new energy catalytic material are close to or similar to those given in Example 1 and will not be repeated here.

[0078] Example 3

[0079] The method is the same as that of Example 1, except that in step 2, 1 g of g-C3N4 is mixed with 1.2 g of sodium thiocyanate to obtain the precursor g-C3N4-1.2CN, and then step 3 is continued to obtain 1.2A BTA -D C3N4 -1.2A CN .

[0080] The A prepared in this example BTA -D C3N4 -A CNThe trends of the SEM images, TEM images, XRD result diagrams, XPS spectra, N2 adsorption-desorption isotherms, UV diffuse reflectance spectra, PL spectra, transient photocurrent response diagrams, in-situ Fourier infrared images and Fourier transform infrared spectra of the new energy catalytic materials are close to or similar to those given in Example 1 and are not repeated here.

[0081] Example 4

[0082] The method is the same as in Example 1, except that in step 3, 0.1 g of the precursor is mixed with 0.1 g of trimesaldehyde to obtain 1A BTA -D C3N4 -A CN .

[0083] The A prepared in this example BTA -D C3N4 -A CN The trends of the SEM images, TEM images, XRD result diagrams, XPS spectra, N2 adsorption-desorption isotherms, UV diffuse reflectance spectra, PL spectra, transient photocurrent response diagrams, in-situ Fourier infrared images and Fourier transform infrared spectra of the new energy catalytic materials are close to or similar to those given in Example 1 and are not repeated here.

[0084] Example 5

[0085] The method is the same as in Example 1, except that in step 3, 0.1 g of the precursor is mixed with 0.14 g of trimesaldehyde to obtain 1.4A BTA -D C3N4 -A CN .

[0086] The A prepared in this example BTA -D C3N4 -A CN The trends of the SEM images, TEM images, XRD result diagrams, XPS spectra, N2 adsorption-desorption isotherms, UV diffuse reflectance spectra, PL spectra, transient photocurrent response diagrams, in-situ Fourier infrared images and Fourier transform infrared spectra of the new energy catalytic materials are close to or similar to those given in Example 1 and are not repeated here.

[0087] Experimental Example 1

[0088] (1) Photocatalytic H2O2 production: In the experiment of photosynthesizing H2O2, a xenon lamp was used as a simulated sunlight source. The specific experimental steps were as follows: 10 mg of catalyst was added to 20 mL of 10 vol% ethanol and 10 mM p-methoxybenzyl alcohol solution and stirred at 350 rpm / min. Before illumination, oxygen was passed through the dark and stirred for 30 min to allow the solution to reach adsorption / desorption equilibrium; a xenon lamp was used as a simulated light source, and the light intensity was 100 mW / cm through a 420 nm filter. 2 After illumination, 1 mL of the suspension was taken using a disposable needle and filtered using a 0.22 μm microporous filter. The obtained transparent filtrate was used to determine the concentration of H2O2 using the iodine ion calibration method.

[0089] (2) Detection of H2O2: 1 mL of C8H5KO4 aqueous solution (0.1 M) and 1 mL of KI aqueous solution (0.4 M) were added to the above transparent filtrate (1 mL) and then kept for 30 minutes. - react to form triiodide anion (I 3- ), which shows a characteristic absorption peak at about 350nm. Therefore, the linear relationship between concentration and absorption value can be obtained by fitting calculation, and the concentration of H2O2 in the catalytic system can be calculated.

[0090] Fig.12 The g-C3N prepared in Example 1 of the present invention is shown 4、 g-C3N4-CN and A BTA -D C3N4 -A CN The performance of new energy catalytic materials in producing hydrogen peroxide, such as Fig.12 As shown, under the same preparation conditions, compared with g-C3N 4、 g-C3N4-CN,A BTA -D C3N4 -A CN The hydrogen peroxide production capacity of new energy catalytic materials has been greatly improved.

[0091] Fig.13 A prepared in Examples 1-5 of the present invention is shown BTA -D C3N4 -A CN New energy catalytic performance of hydrogen peroxide production, such as Fig.13 As shown, under the same conditions, the A provided in Example 1 BTA -D C3N4 -A CN The material ratio with the best effect of producing hydrogen peroxide by new energy catalytic materials is the method described in Example 1.

[0092] Fig.14 A prepared in Example 1 of the present invention is shownBTA -D C3N4 -A CN The production of hydrogen peroxide by new energy catalytic materials under different gas atmospheres, such as Fig.14 As shown, it can be clearly found that the catalyst still has a strong hydrogen peroxide production performance in the air atmosphere, and the hydrogen peroxide concentration and p-anisaldehyde (AA) concentration are the highest when oxygen is used as the gas atmosphere.

[0093] Fig.15 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The effect of the amount of new energy catalytic materials on the production of hydrogen peroxide, such as Fig.15 As shown, under the same conditions, 2.5, 5, 10, 20, and 40 mg of catalyst were added to 20 ml of reaction solution, and the hydrogen peroxide production increased gradually.

[0094] Fig.16 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The production of hydrogen peroxide by new energy catalytic materials at different pH values, such as Fig.16 As shown in the figure, during the photocatalytic H2O2 production process, 0.1M hydrochloric acid (HCl) and 0.1M sodium hydroxide (NaOH) were used to adjust the solution pH to 3, 9, and 11, and then the experiment was carried out. The experimental results show that under the same conditions, the reaction solution with a pH of 9 produces the highest amount of hydrogen peroxide.

[0095] The above verification experimental results show that: oxygen is used as the gas atmosphere, a xenon lamp is used as the light source, and the light intensity is 100mW / cm 2 Under the irradiation of visible light (λ>400nm), the catalyst dosage was 10mg, the concentration of p-methoxybenzyl alcohol was 10mM, the initial temperature was room temperature, and the pH was 9.

[0096] A BTA -D C3N4 -A CN The photocatalytic material produced a hydrogen peroxide concentration of 3.782mmol / L after 60 minutes, which is much higher than that of similar photocatalysts. Moreover, the photocatalytic performance of the material was stable after several reactions, and a large amount of hydrogen peroxide could be produced under long-term illumination, which has practical application value.

[0097] (3) Cyclic experiment: After the first reaction is completed, the solution containing the new energy catalyst is centrifuged, and the lower layer material is dried at 60°C for 8 hours, and then placed in the reactor again for the next photoreaction. Except for the material, the other reaction conditions are the same as the first time; after the second reaction is completed, the above steps are repeated to carry out the third hydrogen peroxide production experiment until the seventh reaction is completed.

[0098] Fig.17 A prepared in Example 1 of the present invention is shown BTA -D C3N4 -A CN The results of the recycling experiment of new energy catalytic materials, such as Fig.17 As shown, after 3 cycles of use, A BTA -D C3N4 -A CN The new energy catalytic material still maintains a high hydrogen peroxide production capacity. When it is recycled for 4-7 times, A BTA -D C3N4 -A CN The hydrogen peroxide production capacity of new energy catalytic materials has declined.

[0099] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0100] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.

[0101] The above is a detailed introduction to a new energy catalyst, a preparation method and an application thereof provided by the present invention. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and the scope of application. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing a new energy catalyst, characterized in that: The preparation method comprises the following steps: S1: After g-C3N4 and sodium thiocyanate are uniformly mixed, they are placed in a nitrogen atmosphere and pyrolyzed at 400-600°C for 3-5h. The reaction product is cooled, washed and dried to obtain the precursor material g-C3N4-CN; S2: The ground precursor g-C3N4-CN and trimesic acid aldehyde are added to an acetonitrile solution for ultrasonic dispersion, and heated in an oil bath at 80-120°C for 10-14h under magnetic stirring. The reaction product is cooled, washed and dried to obtain the new energy catalyst A. BTA -D C3N4 -A CN .

2. The preparation method according to claim 1, characterized in that: In step S1, the step of uniformly mixing g-C3N4 and sodium thiocyanate includes: after mixing g-C3N4 and sodium thiocyanate, adding a small amount of water and stirring to allow sodium thiocyanate to fully contact g-C3N4, and then putting the mixture into an oven for drying.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the mass ratio of g-C3N4 to sodium thiocyanate is between 1:0.5-1.

5.

4. The preparation method according to claim 1, characterized in that: In step S1, the washing and drying treatment includes: washing the reaction product 3-5 times with anhydrous ethanol and deionized water alternately, and then placing the product in an oven and drying it at 50-70°C.

5. The preparation method according to claim 1, characterized in that: In step S2, the particle size of the precursor material g-C3N4-CN after grinding is between 200-400 meshes.

6. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the precursor material g-C3N4-CN to the trimesaldehyde is between 1:1-2.

7. The preparation method according to claim 1, characterized in that: In step S2, the ultrasonic dispersion time is between 0.5 and 1 h; The washing and drying treatment comprises: washing the reaction product with acetonitrile for 3-5 times, and then placing the product in an oven and drying it at 50-70°C.

8. The preparation method according to claim 1, characterized in that: The g-C3N4 is obtained by calcining melamine as a raw material in an air atmosphere; The calcination temperature is between 500-600° C. and the calcination time is between 3-6 hours.

9. A new energy catalyst obtained by the preparation method described in any one of claims 1 to 8.

10. An application of a new energy catalyst obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The new energy catalyst is used to catalyze air / oxygen to produce hydrogen peroxide; In the process of catalyzing air / oxygen to produce hydrogen peroxide, p-methoxybenzyl alcohol is used as an electron donor.

Citation Information

Patent Citations

  • Cyano-functionalized g-C3N4 colloid catalyst as well as preparation method and application thereof

    CN113117721A

  • Modified carbon nitride nanosheet material for photocatalytic degradation of pollutants and production of hydrogen peroxide and preparation method of modified carbon nitride nanosheet material

    CN114870878A